A systematic review of the complications of contemporary total elbow arthroplasty. (October 2021) - Parker, Phoebe; Furness, Nicholas D; Evans, Jonathan P; Batten, Timothy; White, William J; Smith, Christopher D
Background: Total elbow arthroplasty is a low volume procedure. We aimed to evaluate complication rates and cumulative percentages associated with the most frequently used contemporary implants and for the commonest indications. Methods: A systematic literature search of all studies reporting complications following total elbow arthroplasty with 12-month minimum follow-up was undertaken. Quality of studies was assessed with the Methodological-Index-for-Non-Randomised-studies criteria. British NJR data identified the most common UK prostheses and indications. The complication rates for all undesirable events contributing to patient outcome were extracted and cumulative percentages were calculated. Results: One hundred seventeen studies were screened, 12 studies included, totalling 815 procedures. Mean follow-up was 3.8 years. The overall complication cumulative percentage was 60.7%, significantly higher than that seen in other joint arthroplasty, including a 6.5% deep infection rate. Nerve injury was comparable between implants at around 4.1%. Radiographic loosening had a cumulative rate of 17.2%. Revision for symptomatic aseptic loosening was 6.3%. Conclusions: This is the largest systematic review of the complications of total elbow arthroplasty. Surgeons should be aware of differing complications related to their implant of choice, each having its own specific complication. Trauma as an indication appears to have an increased complication rates compared to inflammatory arthropathy. There is a lack of literature regarding the independent results of osteoarthritis as a specific indication for total elbow arthroplasty.